Carvacrol biofumigation provides effective postharvest control of litchi downy blight by disrupting the structure and metabolism of Peronophythora litchii - Hongjun Ge; Lanning Wang; Jingkun Lv; Siyuan Xie; Chao Wang; Chun Xiao; Wanke Sheng; Sihan Cheng; Zhiyuan Yin; Danyu Shen; Daolong Dou (Postharvest Biology and Technology, 2026)

Green synthesis of N-doped hierarchical porous biochar from Artemisia leaf for enhanced peroxydisulfate activation: Synergistic roles of edge nitrogen and carbonyl group - Lin Ge; Zhan Chen; Yuan Pan; Xiansheng Zhang; Teng Li; Xinyi Huang; Binbin Shao; Sheng Liu; Yunze Wang; Yu Zhang; Zhifeng Liu (Environmental Research, 2026)

The JAK/STAT pathway: a pivotal therapeutic target in disease and advances in natural product modulation - Ming-Yue Li; Yu-Yang Lin; Chun-Ying Wang; Yu-Shan Qi; Jun-Sheng Zhang; Di Ge; Hai-Na Yu; Hua Zhang; Jie Bao (Molecular Diversity, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Predefined-time global prescribed performance tracking of ASV via adaptive event-triggered control - Peng Chen; Tao Han; Bo Xiao; Yuan Tan; Xi-Sheng Zhan; Ming-Feng Ge (Ocean Engineering, 2026)

Metal-phenolic microcapsules-reinforced hydrogel-based in situ tumor vaccine for postoperative adjuvant therapy - Xin Tan; Renwang Sheng; Yanling Liang; Yinghua Tao; Weikun Li; Nuoya Chen; Diyi Feng; Xinyang Pan; Shuangshuang Ma; Fangzhou Liu; Ling Liu; Liqin Ge (Chemical Engineering Journal, 2026)

Elucidating functional group governance for catalytic synthesis of bio-based aromatic amines - Ge-liang Xie; Yu Luo; Kai-cheng Xia; Sheng-ren Li; Lujiang Xu; Zhen Fang (Biomass and Bioenergy, 2026)

Characterization of an Endophytic Fusarium odoratissimum Strain 25# from Dysosma versipellis with Putative Podophyllotoxin Production - Xiao-Ming Tan; Zheng-Hu Guo; Xiang-Hua Xia; Xin-Yi Xie; Wen-Tao Tan; Chang-Ge Yuan; Yun-Sheng Wang; Ya-Qin Zhou (Current Microbiology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Study on temperature evolution and associated phase behavior inside an industrial-scale large-diameter test pipeline during liquid CO₂ discharge - Xin Ouyang; Zichao Hu; Tao Wang; Qiqi Liu; Sheng Sun; Ran Sun; Shiqi Ge; Zhenyi Liu (Process Safety and Environmental Protection, 2026)

Research on high-efficiency region and condition of pectoral fin - Chaowu Sheng; Liwen Nan; Qiaoling Gao; Jiawang Chen; Ziqiang Ren; Han Ge; Haocai Huang (Ocean Engineering, 2026)

A theoretical model for local buckling of FRP-confined CFST columns - Yue-Ling Long; Xiang-Hua Yue; Sheng Ge; Leroy Gardner; M. Ahmer Wadee (Engineering Structures, 2026)

Reduce-order dynamic modeling of X-braced girder considering flexible joints for analytical vibration characteristic investigation - Mei Liu; Huaqiang Ge; Lishan Ma; De Li; Zunbing Sheng (Advances in Space Research, 2026)

Polygonatum kingianum polysaccharides delay aging through UPRmt-mediated regulation of mitochondrial function and intestinal homeostasis - Jing-Juan Yang; Sheng-Lan Zhao; Ya-Ge Ma; Jian-Guo Jiang; Xi Zhang (Food Bioscience, 2026)

Study on the VOCs-induced odor pollution and health risks in a typical industrial area of Eastern China - Lingling Zhang; Xiaofeng Xu; Xia Sheng; Haiwei Li; Wen Tan; Xinyuan Xu; Yayi Zhang; Xuyun Zhang; Jian Wu; Hualong Liu; Xinyu Zhao; Xinlei Ge (Atmospheric Environment, 2026)

Complete genome sequence of a novel carlavirus infecting Passiflora edulis in China - Luping Zheng; Huoyang Ge; Xiaoyue Liu; Shiwei Zhang; Chaowei Yu; Furong Liao; Jianguo Sheng; Ruhui Li (Archives of Virology, 2026)

Impact Mechanical Behavior and Energy Dissipation Analysis of Rock-Concrete Composites with different Interface Roughness - Wei-jing Yao; Han-bing Xu; Sheng-qi Yang; Shao-ge Rui; Jian-yong Pang (Applied Geophysics, 2026)

Distribution characteristics and release flux estimation of nitrogen and phosphorus in sediments of Liangzi Lake, China - Junjie Hu; Yuxin Hu; Sheng Hu; Ge Li; Xiaoguo Chen; Zhi Wang (Environmental Science and Pollution Research, 2026)

Correction to: Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Microbial Community Traits and Necromass Dynamics Shape Soil Carbon Accumulation - Wankun Pan; Sheng Tang; Wolfgang Wanek; Zhongkui Luo; Ji Chen; Yuanhe Yang; Tida Ge; Karina A. Marsden; Guopeng Liang; David R. Chadwick; Xinping Chen; Andrew S. Gregory; et al. (Global Change Biology, 2026)
Soil organic carbon (SOC) sequestration is vital for food security and climate mitigation. However, its long‐term response to fertilisation remains unclear. Using the 180‐year Broadbalk Experiment (the world's longest‐running fertilisation trial; Rothamsted, UK), combined with 14 C labelling and metagenomics, we identified fundamentally distinct mechanisms of SOC accumulation: a microbially mediated dual pathway under organic fertilisation versus a resource‐limited pathway under inorganic fertilisation. Sustained organic inputs matched inorganic fertilisers in maintaining crop yields while increasing total SOC by 160% (relative to a no‐fertilisation control), far exceeding the 26% gain under inorganic fertilisation. Mechanistically, the continuous supply of labile organic matter provided an energetic surplus, allowing copiotrophic microbial communities with high carbon use efficiency to reduce investment in energy‐intensive enzyme synthesis. This metabolic efficiency facilitated a dual‐pathway expansion, elevating dynamic particulate organic carbon (POC) from 1.4 to 7.5 g kg −1 , while microbial assimilation and necromass accumulation concurrently increased mineral‐associated organic carbon (MAOC) from 6.8 to 21.5 g kg −1 . Conversely, inorganic fertilisation induced an oligotrophic ‘mining’ strategy, in which microorganisms upregulated the degradation of complex organic matter under carbon‐limited conditions, restricting sustained SOC accumulation primarily to the MAOC pool. A global meta‐analysis of field experiments (0–120 years) corroborated these temporal trajectories across diverse soil types, showing that SOC under organic fertilisation increases in a time‐dependent manner, reaching a 77% gain after 80 years (three‐fold greater than under inorganic inputs). Overall, organic fertilisation enhances total SOC via POC and MAOC accumulation, whereas inorganic fertilisation mainly increases MAOC. Long‐term SOC persistence depends not only on carbon inputs, but also on microbial community traits and necromass dynamics, suggesting that aligning nutrient inputs with these biological mechanisms is critical for sustainable carbon sequestration.

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Enhanced Remediation of Thiamethoxam Contaminated Soil by Biochar-Immobilized Enterobacter Cloacae TMX-6: Physicochemical Property Regulation and Microbial Response - Yaoyao Cao; Hui Zhang; Jian Chen; Jing Ge; Hongjie Sheng; Qun Wan; Liya Ma; Fayun Feng; Kang Lv; Xiangyang Yu (Water, Air, & Soil Pollution, 2026)

Damage observation-informed seismic vulnerability assessment of stainless steel-reinforced concrete bridge piers - Xiao Ge; Jian-Cheng Dai; Dong-Sheng Wang; Jing-Jing Zhang; Yu-He Zou; Yan-Hui Liu (Bulletin of Earthquake Engineering, 2026)

Predicting Remaining Oil Saturation in Complex Carbonate Reservoirs via Constrained BSEM Inversion and an IP-Inclusive Saturation Model - Yao Lu; Zu-Zhi Hu; Wei Wan; Ya-Neng Luo; Guo Zhao; Ke Yang; Shuai-Yin Ge; Zhan-Xiang He; Yun-Sheng Zhao (Applied Geophysics, 2026)

A Soft Bionic Pectoral Fin Actuated by a Series of Differential Gear Units - Chaowu Sheng; Liwen Nan; Qiaoling Gao; Jiawang Chen; Peng Zhou; Han Ge; Haocai Huang (Journal of Marine Science and Engineering, 2026)
The bionic pectoral fin serves as the primary propulsion component of ray-inspired robots. In our previous research, a motion equation was proposed for the real pectoral fin, which can be modeled as a series of NACA airfoil-shaped cross-sections distributed along the spanwise direction. Each cross-section undergoes two coupled rotational motions about its chord line and spanwise rotational axis. To achieve this type of motion, this article introduces a novel bionic pectoral fin mechanism driven by a series of differential gear units. The differential unit generates two coupled rotational motions corresponding to the cross-section of the pectoral fin in motion. A series of interconnected differential units provides a unique topology for the bionic mechanism and can generate a diverse range of motions. Through kinematic analysis, the motion equation was mapped onto the rotational angles of motors in the differential units. The proposed bionic mechanism was then fabricated and subjected to experimental test, demonstrating its effectiveness with a maximum thrust of 0.71 N. The distinctive structure of this bionic mechanism differentiates it from conventional designs and is expected to provide some inspiration for bionic pectoral fins and ray-inspired robots.

Research on real time mapping and transfer learning based 3D semantic segmentation of unstructured orchards - Sipei Li; Sheng Wen; Fagang Liu; Haiyan Zhang; Yufeng Ge; Zhiyin Deng (Computers and Electronics in Agriculture, 2026)

Flux dynamics and scenario simulation of PFAS under extreme hydrological perturbations in urban tributary flowing into the Yangtze River: A focus on floods - Hui Xiao; Ge Tang; Sheng Zhang; Zeqiang Wu; Qi Liu; Shaoyan Feng; Yifan Fan; Tong Liu; Xin Qian; Huiming Li (Journal of Hazardous Materials, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Comparative study on the mechanisms of citrus pectin and polygalacturonic acid in alleviating food allergies - Xin Liu; Xiang Tan; Sheng Tang; Feiyang Yang; Ge Wang; Wenjue Gao; Junying Bai; Linhua Huang (Carbohydrate Polymers, 2026)

Ethambutol induces optic neuropathy through SDHB-mediated ferroptosis in retinal ganglion cells via Smad4 pathway - Qiushi Li; Wei Ge; Yifan Zhang; Qibin Xu; Junli Xu; Yu Zhang; Xingneng Guo; Wenyan Sheng; Liwei Zhu (Human Cell, 2026)
Ethambutol (EMB)-induced optic neuropathy (EON) is a clinical concern. Ferroptosis, involving iron and toxic reactive oxygen species (ROS), causes unique cell death, but its mechanism in EON is unclear. This study aims to explore the EON mechanisms. Wistar rats were used to establish an EON model by administering EMB at 50 mg/kg daily for 8 weeks. Retinal ganglion cells (RGC-5 cells) were used for in vitro experiments. Histological staining, MTT assays, flow cytometry, western blot analysis, dual-luciferase reporter assay, chromatin immunoprecipitation, and high-throughput sequencing were conducted to investigate cell death modes and molecular changes. EMB treatment leads to significant cell loss and structural damage in RGCs of EON model, predominantly through ferroptosis. We confirm increased ROS levels, downregulation of SLC7A11 and GPX4, and decreased glutathione (GSH) levels, upregulation of malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE) levels in EMB-treated RGC-5 cells. Furthermore, sequencing data reveal that in RGC-5 cells treated with EMB, the differentially expressed genes (DEGs) primarily exhibited alterations in biological functions associated with metabolism, stress response, and apoptotic regulation. Specifically, EMB inhibits the expression of succinate dehydrogenase enzyme B (SDHB), thereby disrupting antioxidant defenses and facilitating ferroptosis. Moreover, Smad4 has been pinpointed as a pivotal transcription factor in regulating SDHB expression. Notably, its interaction with the promoter region of SDHB is inhibited by EMB. This study provides compelling evidence for the involvement of ferroptosis in EON and highlights SDHB and Smad4 as potential therapeutic targets for mitigating this adverse effect.

Antimony induces oxidative stress to impair enteroendocrine cells and disrupt glucose homeostasis - Lanfei Jin; Longtao Zhu; Chengdong Wu; Weiqiong Jin; Ke Liu; Junxuan Peng; Xin Xu; Xiaolong Ge; Ying Zhu; Xiaole Sheng; Rongpan Bai; Guangdi Chen (Journal of Hazardous Materials, 2026)

Longitudinal monitoring of global prevalence, genomic characterization and transmission routes of Salmonella Derby strains from food, humans and the environment - Min-Ge Wang; Dong-Xiao Ru; Ying-Xin Ruan; Ying Chu; Peng-Yu Zhang; Sheng Chen; Ruan-Yang Sun (Food Research International, 2026)

Enhanced microalgal-bacterial granulation via a novel two-stage strategy: initial Microthrix parvicella-induced limited filamentous bulking and subsequent hydrodynamic-phototrophic synergy - Mengting Li; Zhipeng Chen; Zhaoming He; Sheng Yu; Weican Shi; Qian Bi; Xiang Li; Jiaqi Hu; Shuang Qiu; Shijian Ge (Bioresource Technology, 2026)

Artificial intelligence, environmental regulation and urban sustainable development: an empirical analysis of 287 cities in China - Kai Dong; Yang Ge; Tianxiang Sheng; Qianyun Weng; Jiaming Miao; Yanxin Cheng (Clean Technologies and Environmental Policy, 2026)

ICFMNet: an automated segmentation and 3D phenotypic analysis pipeline for plant, spike, and flag leaf type of wheat - Pengliang Xiao; Sheng Wu; Shiqing Gao; Weiliang Wen; Chuanyu Wang; Xianju Lu; Xiaofen Ge; Wenrui Li; Linsheng Huang; Dong Liang; Xinyu Guo (Computers and Electronics in Agriculture, 2025)

Methylsiloxanes in drinking water treatment plants: Occurrence, removal efficiencies and exposure risks across multiple stages of treatment process development - Yimeng Zhang; Zhenyang Yu; Jing Yang; Ge Yin; Yanbin Zhao; G․Daniel Sheng; Daqiang Yin (Water Research, 2025)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Comparative assessment of real-world vehicle particulate emissions: Brake wear versus exhaust emissions - Changyu Wang; Chenyu Song; Wenfeng Xie; Aihong Li; Wanyi Chen; Yitu Lai; Sheng Su; Yachao Wang; Yunshan Ge (Journal of Cleaner Production, 2025)

Dialysis-assisted control significantly enables stable long-term unaerated partial nitrification in a microalgal-bacterial consortium treating hydrolyzed urine - Zimu Li; Zhipeng Chen; Yue Xie; Yanbing Hu; Shiling Xu; Sheng Yu; Shuang Qiu; Shijian Ge (Bioresource Technology, 2025)

FoxO1 regulates human haematopoietic stem cells self-renewal and engraftment - Lieguang Chen; Qunfang Ge; An Wu; Shasha You; Lixia Sheng; Yanli Lai; Yurong Bao; Congfa Jiang (Molecular Biology Reports, 2025)

Numerical Analysis of a Vertical Axis Wind Turbine with Racetrack Trajectory - Sixiong Ge; Yan Yan; Zhecheng Lou; Jie Xu; Zhehao Sheng; Jiahuan Cui (Journal of Marine Science and Engineering, 2025)
This study presents a comprehensive numerical and theoretical analysis comparing the aerodynamic performance of a racetrack trajectory vertical axis wind turbine with a baseline VAWT. The racetrack trajectory comprises two parallel straight segments connected by semicircular arcs. However, two critical research gaps remain: the aerodynamic performance of this non-axisymmetric rotor, especially its sensitivity to inflow direction, is not well understood, and a computationally efficient theoretical model for its rapid design is lacking. Using unsteady Reynolds-Averaged Navier–Stokes (URANS) simulations to systematically quantify this sensitivity, and developing an adapted double multiple streamtube (DMST) model, the performance of both turbines is evaluated across tip speed ratios (TSRs) of 1.5–4 and inflow angles β = 0–90°. Results indicate that the racetrack turbine achieves a peak power coefficient of 0.49 at TSR = 2.5 and β = 90°, 16.7% higher than the baseline VAWT. Its performance is highly sensitive to inflow direction, whereas the baseline operates more uniformly across angles. Flow field and wake analyses reveal that the racetrack turbine exhibits faster wake recovery and lower turbulence intensity downstream under optimal inflow. This study demonstrates the potential of racetrack turbines for enhanced directional efficiency in marine wind conditions and validates the adapted DMST model as a reliable tool for preliminary design.

Alkaloids from the tubers of Pinellia pedatisecta - Xu Chen; Yan-gang Cao; Feng-xiao Hao; Yan-ling Liu; Fang-ge Chi; Ying Niu; Di Lu; Bing-xian Zhao; Lan Chen; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Norsesquiterpenes from the stems and leaves of Pinellia pedatisecta Schott - Xu Chen; Yan-gang Cao; Fang-Ge Chi; Yan-ling Liu; Kai-li Ye; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Enhanced insecticidal activity and bioavailability of thiacloprid from pH-responsive porous MPN(Fe)@ZIF-8 nanocarrier - Miao Wang; Donghui Xu; Ying Zhang; Jie Zhou; Zhihao Lin; Yiming Zhao; Xin Ding; Bin Sheng; Xiaobin Wen; Xiao Song; Ge Chen; Xiaomin Xu; et al. (Journal of Cleaner Production, 2025)

Sodium alginate-synthesizing regulatory gene algB in Pseudomonas putida XMS-1 decreases Cd uptake in Allium tuberosum in the Cd-polluted soil - Yanyan Ge; Zhenyu Wen; Xuan Liu; Zhihui Xiong; Xiafang Sheng (Journal of Environmental Sciences, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

Boosting photochromism and room-temperature-phosphorescence for multi-dimensional dynamic encryption via donor–acceptor anion–π interaction - Yang Hua; Jian-Ge Zeng; Chun-Jie Liu; Ming-Sheng Wang; Li Li (Chemical Engineering Journal, 2025)

Chemical constituents from the tubers of Pinellia pedatisecta Schott - Fang-Ge Chi; Xu Chen; Yan-Gang Cao; Yan-Ling Liu; Di Lu; Ying Niu; Bing-Xian Zhao; Lan Chen; Yi-Xin Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Natural Product Research, 2025)

The Identification and Synthesis of New Sea Cucumber Peptides Leveraging Peptidomics Technology, along with their Anti-Parkinson’s Disease Efficacy - Jiawei Liu; Yusheng Shi; Lingling Jin; Baixue Sun; Ruonan Wang; Guangbo Ge; Guanghao Zhu; Xiaolin Cui; Jie Zhao; Yan Zhang; Sheng Li (Journal of Neuroimmune Pharmacology, 2025)

Heavy metal release from two typical tire microplastics under different simulated environments and bioavailability assessment in China - Zhuanxi Luo; Ning Wang; Xinyi Zhou; Ao Ge; Yanhua Wang; Sheng Su; Yitu Lai; Ruilian Yu; Zhenhong Wang (Environmental Pollution, 2025)

Laser-assisted photonic crystal-based thermal printing: A technology with significant improvements in resolution, grayscale, color tuning, and compatibility with curved substrate - Tian Yin; Sheng Chen; Xiaodong Lu; Jianping Ge (Chemical Engineering Journal, 2025)

Unraveling the molecular mechanisms of paraquat toxicity: The interplay of ATF4, ferroptosis, and endoplasmic reticulum stress - Jingjing Ke; Qiqi Cai; Xiaogang Ge; Sheng Zhang (Food and Chemical Toxicology, 2025)

Advance and perspective of carbon-based aerogels and their composites - Yanfeng Fu; Hui Ye; Ke Yuan; Qinxin Wang; Longhui Ge; Sheng Cui (Chemical Engineering Journal, 2025)

Production of phytoliths and phytoc in above- and belowground parts of common reed (Phragmites australis) in a riverine wetland of the Yellow River Delta, China - Li Zhang; Wenyi Sheng; Huijia Song; Lele Liu; Weihua Guo; Yuzhi Wang; Changzi Ge (Journal of Soils and Sediments, 2025)

Symmetrical response of plant diversity but asymmetrical response of biomass production to rainfall reduction and addition in global grasslands - Ge Li; Xu-Long Zhang; Josep Peñuelas; Jordi Sardans; Ying Zhao; Yan Yu; Jian-Sheng Ye (Plant and Soil, 2025)

Long-term manure and mineral fertilisation drive distinct pathways of soil organic nitrogen decomposition: Insights from a 180-year-old study - Wankun Pan; Sheng Tang; Jingjie Zhou; Wolfgang Wanek; Andrew S. Gregory; Tida Ge; Karina A. Marsden; David R. Chadwick; Yongchao Liang; Lianghuan Wu; Qingxu Ma; Davey L. Jones (Soil Biology and Biochemistry, 2025)

Biofilm-overproducing Bacillus amyloliquefaciens strain B9ΔywcC reduces cadmium uptake in lettuce by upregulating the expression of proteins associated with root surface biofilm formation and cell membrane homeostasis - Lijing Sun; Rongrong Gao; Qian Zeng; Zhanbiao Ge; Xiafang Sheng; Linyan He (Journal of Hazardous Materials, 2025)

Occurrence, temporal, and spatial variation of PPCPs and EDCs in typical drinking water sources and tap water in southern China - Nan Gai; Ge Feng; Huilun Chen; Guohui Lu; Haitao Piao; Qifeng Tang; Sheng Chang; Jiuchen Liu (Journal of Environmental Chemical Engineering, 2025)

Fungal xylomannan as a dietary supplement: Activates hepatic AMPK/HIF1α signaling to attenuate insulin resistance - Yuhan Meng; Xiushi Jia; Lujuan Zheng; Min Wang; Jing Xia; Mingming Li; Junzhu Wei; Yanchen Qi; Chen Meng; Jiaxing Sheng; Pengyu Ge; Yuying Fan; et al. (Food Bioscience, 2025)

Strong heterogeneity in laterally exchanged particulate organic matter across tidal marshes in a large river delta - Qi Wu; Hong-Sheng Cao; Youhei Yamashita; Christian Lønborg; Run Li; Jianzhong Ge; Hualei Yang; Bolin Liu; Jinzhou Du; Fang Cao (Environmental Research, 2025)

The restoration of soil multifunctionality in the later stages of biocrust succession is related to bacterial niche expansion: a case study of ion-adsorption rare earth tailings in southern China - Sheng Xu; Shifeng Sun; Huimin Qiu; Dan Lu; Yizhen Liu; Jun Ye; Hui Zhong; Tao Wang; Yanan Zhang; Lan Wu; Chi Yao; Qiying Cai; et al. (Plant and Soil, 2025)

Physiological and genetic responses of Chlorella sp. to nitrite accumulation in microalgal-bacterial consortium with partial nitrification treating municipal wastewater - Mengting Li; Zhipeng Chen; Xiang Li; Sheng Yu; Shiling Xu; Shuang Qiu; Shijian Ge (Water Research, 2025)

Comparative study on the alleviating effect of neohesperidin dihydrochalcones and its synthetic precursor neohesperidin on ovalbumin-induced food allergy - Xin Liu; Chen Wang; Sheng Tang; Ge Wang; Yaoxin Huang; Feiyang Yang; Xiang Tan; Junying Bai; Linhua Huang (Food Research International, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

Diketopiperazine and purine alkaloids from the tubers of Pinellia pedatisecta Schott and their protective activities against Aβ25-35-induced PC-12 cell injury - Xu Chen; Yan-gang Cao; Feng-xiao Hao; Yan-ling Liu; Fang-ge Chi; Ying Niu; Di Lu; Bing-xian Zhao; Lan Chen; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Static Stress Triggering Effect on the Surrounding Major Faults and Aftershocks of the 2024 M 7.4 Earthquake in Hualien, Taiwan - Shu-Zhong Sheng; Zi-Fei Mi; Xiao-Juan Zhang; Kun-Peng Ge (Applied Geophysics, 2025)

Spatial-temporal variations of kelp 129I contents in coastal waters of China before and after the Fukushima Daiichi Nuclear Power Plant accident - Xiaowen Liu; Jialin Liu; Yukun Fan; Guozhi Xie; Xiaole Sun; Luyuan Zhang; Qi Liu; Xiaoqi Yang; Delin Duan; Fangli Qiao; Chang Zhao; Baozhu Ge; et al. (Marine Pollution Bulletin, 2025)

Combination of NRPS/PKS tuning and morphological engineering enhanced iturin A production in Bacillus amyloliquefaciens - Zheng-Jie Hou; Hai-Meng Lai; Kai-Ge Song; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng (Chemical Engineering Journal, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Engineering microcapsules with immune modulatory properties: Applications in cancer, inflammation, and autoimmunity - Xin Tan; Renwang Sheng; Liqin Ge (Chemical Engineering Journal, 2025)

A calculation method for cotton phenotypic traits based on unmanned aerial vehicle LiDAR combined with a three-dimensional deep neural network - Xiaoshuai Chen; Sheng Wen; Lei Zhang; Yubin Lan; Yufeng Ge; Yongjian Hu; Shaoyong Luo (Computers and Electronics in Agriculture, 2025)

LettuceP3D: A tool for analysing 3D phenotypes of individual lettuce plants - Xiaofen Ge; Sheng Wu; Weiliang Wen; Fei Shen; Pengliang Xiao; Xianju Lu; Haishen Liu; Minggang Zhang; Xinyu Guo (Biosystems Engineering, 2025)

Improving the catalytic activity and sintering resistance of Ni-BaCe0.7Zr0.1Y0.1Yb0.1O3−δ cermet anode for ammonia-fueled protonic ceramic fuel cells via Cobalt addition - Bangze Wu; Xiaole Yu; Zenan Zhao; Bingyu He; Zhanheng Jin; Zhexiang Yu; Qing Ni; Shoucheng He; Han Chen; Yifeng Zheng; Sheng Cui; Lin Ge (Chemical Engineering Journal, 2025)

Production and Subsequent Application of Different Biochar-based Organic Fertilizers to Enhance Vegetable Quality and Soil Carbon Stability - Jining Zhang; Li-ao Ge; Yuxiang Yang; Xianxian Zhang; Cong Wang; Huifeng Sun; Honghui Chen; Jian Huang; Sheng Zhou (Journal of Soil Science and Plant Nutrition, 2025)

Using machine learning to predict soil lead relative bioavailability - Shuang Zhang; Xiaoping Li; Tunyang Geng; Yu Zhang; Weixi Zhang; Xueming Zheng; He Sheng; Yueheng Jiang; Pengyuan Jin; Xuelian Kui; Huimin Liu; Ge Ma; et al. (Journal of Hazardous Materials, 2025)

Carbon emissions assessment of ultra-high performance concrete in construction industry: Calculation method and case study - Sheng Li; Ge Han; Boshi Du; Zhisheng Jiang; Linqi Sun (Energy and Buildings, 2025)

Intensifying bioconversion of rich-capsaicinoids food waste into fengycin by the tolerant-artificial consortium - Tian-Xu Duan; Kai-Ge Song; Hui-Zhong Sun; Wei Shang; Jing-Sheng Cheng (Chemical Engineering Journal, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Investigation into the Motion Characteristics and Impact Loads of Buoy Water Entry Under the Influence of Combined Waves and Currents - Wei Ge; Xiaolong Ying; Hailong Chen; Sheng Wu; Jian Zhang; Lixue Jiang; Hengxu Liu (Journal of Marine Science and Engineering, 2025)
As a crucial component in marine monitoring, meteorological observation, and navigation systems, studying the motion characteristics and impact loads of buoy water entry is vital for their long-term stability and reliability. When deployed, buoys undergo a complex motion process, including the impact of entering the water and a stable floating stage. During the water entry impact phase, the motion characteristics and impact loads involve interactions between the buoy and the water, the trajectory of motion, and dynamic water pressure, among other factors. In this paper, the VOF model is used to calculate the buoy’s water entry motion characteristics, and then the STAR-CCM+&ABAQUS bidirectional fluid–structure interaction (FSI) method is used to calculate the water entry impact load of the buoy under different water surface conditions and different initial throwing conditions, considering the influence of the flow field on the structure and the influence of the structure deformation on the flow field. The study finds that under the influence of wave and current impacts, changes in wave height significantly affect the buoy’s heave motions. Under different parametric conditions, due to the specific direction of wave and current impacts, the buoy’s pitch amplitude is relatively more intense compared to its roll amplitude, yet both pitch and roll motions exhibit periodic patterns. The buoy’s pitch motion is sensitive to changes in the entry angle; even small changes in this angle result in significant differences in pitch motion. Additionally, the entry angle significantly impacts the peak vertical overload on the buoy. Instantaneous stress increases sharply at the moment of water entry, particularly at the joints between the crossplate and the upper and lower panels, and where the mast connects to the upper panel, creating peak stress concentrations. In these concentrated stress areas, as the entry speed and angle increase, the maximum equivalent stress peak at the monitoring points rises significantly.

RETRACTED: Wang et al. Amplitude and Phase Computable Ocean Wave Real-Time Modeling with GPU Acceleration. J. Mar. Sci. Eng. 2022, 10, 1208 - Guigui Wang; Shihan Tan; Ge Song; Sheng Wang (Journal of Marine Science and Engineering, 2025)
The journal retracts the article titled “Amplitude and Phase Computable Ocean Wave Real-Time Modeling with GPU Acceleration” [...]

Tectono-sequence evolution of an extensional strike-slip composite basin, a case study of the Miaoxi'nan sub-sag in the eastern Bohai Bay Basin - Sheng Fu; Haifeng Yang; Lijun Song; Wei Zhou; Jiawang Ge; Yanqin Guo (Marine and Petroleum Geology, 2025)

7-Hydroxycoumarin and its conjugated metabolites interact with organic anion transporters 1 and 3 in vitro and in vivo - Lijun Luo; Yongchun Chang; Weilin Zhang; Xiao Liu; Junpu Ge; Jieyi Chen; Yan Li; Dan Zhang; Li Sheng (Chemico-Biological Interactions, 2025)

Alkaline tolerance in plants: The AT1 gene and beyond - Yuting Qi; Yujie Xie; Mingrui Ge; Wei Shen; Yu He; Xiao Zhang; Feng Qiao; Xing Xu; Quan-Sheng Qiu (Journal of Plant Physiology, 2024)

Hybrid pasteurization strategy for energy conservation and quality preservation in cloudy apple juice processing - Lei Ge; Fangting Jia; Jiangtao Yu; Hongyun Liu; Ruxue Bai; Sheng Li; Haihua Wang; Zhenyu Li (Journal of Food Engineering, 2024)

NHX5/NHX6/SPY22 complex regulates BRI1 and brassinosteroid signaling in Arabidopsis - Jun Shang; Guoxiu Mu; Yuting Qi; Xiao Zhang; Wei Shen; Yujie Xie; Mingrui Ge; Yu He; Feng Qiao; Quan-Sheng Qiu (Journal of Plant Physiology, 2024)

Effect of climate warming on subsurface temperature in basins with topography-driven groundwater flow - Yi-Peng Zhang; Xiao-Wei Jiang; Shemin Ge; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Lizhi Wang; Qing Liu; Li Wan (Journal of Hydrology, 2024)

The quorum sensing SinI/SinR-TraI/TraR systems promote Pb stabilization by Ensifer adhaerens S24 in the Pb-polluted aquatic environment - Yanyan Ge; Qi Sheng; Lijing Sun; Linyan He; Xiafang Sheng (Journal of Hazardous Materials, 2024)

Anthropogenic-driven changes in concentrations and sources of winter volatile organic compounds in an urban environment in the Yangtze River Delta of China between 2013 and 2021 - Zihang Zhang; Yunjiang Zhang; Sheng Zhong; Jie Fang; Baoru Bai; Cheng Huang; Xinlei Ge (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Dynamic Response of Roadbed Soil Under Various Dynamic Load Waveforms - Xin-Sheng Zhang; Yan-Ge Chen; Chang-Biao He; Zhen Li; Lei Liao; Yun Cheng; Yin-Lei Sun (Geotechnical and Geological Engineering, 2024)

Photoelectric synaptic device based on Cu2ZnSnS4/ZnO heterojunction for non-volatile vision memory - Shuaifei Mao; Jiantong Ge; Lingling Zhang; Yannan Dai; Sheng Jiang; Yafei Chen; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2024)

Principles, challenges, and optimization of indigenous microalgae-bacteria consortium for sustainable swine wastewater treatment - Sheng Yu; Zhipeng Chen; Mengting Li; Shuang Qiu; Zhe Lv; Shijian Ge (Bioresource Technology, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Water addition but not reduction alters plant biomass–diversity relationship - Yan Yu; Josep Peñuelas; Jordi Sardans; Jiu‐ying Pei; Ge Li; Guo‐lin Liu; Jian‐Sheng Ye (Global Change Biology, 2024)
The relationship between plant aboveground biomass and diversity typically follows a unimodal pattern, showing a positive correlation in resource‐poor habitats and a negative correlation in resource‐rich environments. Precipitation is a crucial resource for both plant biomass and diversity in terrestrial ecosystems. However, the impact of precipitation changes on the relationship between plant biomass and diversity remains unclear. We conduct a water addition field experiment in a semiarid grassland and identify a unimodal relationship between plant biomass and species richness under ambient conditions. Water addition delays the declining phase of this unimodal curve and shift it upward compared to ambient conditions. Our meta‐analysis of water addition experiments conducted across major biomes worldwide (grassland, shrubland, desert, and forest) supports this finding, while water reduction does not alter the biomass–diversity relationship. Water addition increases biomass in all climate but only increases species richness in arid and semiarid climate. Similarly, water reduction decreases biomass in all climate but only reduces species richness in arid and semiarid climate. Species richness in dry subhumid and humid climate does not change significantly. Furthermore, our field experiment shows that water addition increases plant diversity while decreasing soil inorganic nitrogen levels. The increase in one resource, such as water, leads to the scarcity of another, such as nutrient, thus postponing the declining phase of the plant biomass–diversity relationship typically observed in resource‐rich habitats. Our research contributes to predicting the plant biomass–diversity relationship under changing precipitation conditions and highlights the complex interplay between water availability, nutrient level, and plant diversity.

SLC11A1 promotes kidney renal clear cell carcinoma (KIRC) progression by remodeling the tumor microenvironment - Ding Wu; Yulin Zhou; Xiuquan Shi; Xiaoming Yi; Zhengcheng Sheng; Li Fan; Jingping Ge; Wen Cheng; Wenquan Zhou; Haowei He; Dian Fu (Toxicology and Applied Pharmacology, 2024)

Distribution and spatial variation of volatile methylsiloxanes in surface water and wastewater from the Yangtze River Basin, China - Yimeng Zhang; Ge Yin; G. Daniel Sheng; Zhenyang Yu; Daqiang Yin (Science of The Total Environment, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Ionic liquid-based advanced porous organic hyper-crosslinked polymers (ILHCPs) for CO2 capture and conversion - Ruina Zhang; Guokai Cui; Xiuqin Wang; Yinfeng Chen; Xinjie Qiu; Quanli Ke; Dongshun Deng; Chunliang Ge; Hanfeng Lu; Sheng Dai (Chemical Engineering Journal, 2024)

The quorum sensing SinI/R system contributes to cadmium immobilization in Ensifer adhaerens NER9 in the cadmium-contaminated solution - Lijing Sun; Qi Sheng; Yanyan Ge; Linyan He; Xiafang Sheng (Journal of Hazardous Materials, 2024)

Macroencapsulated Al-Si phase change materials for high temperature latent thermal energy storage - Yunqi Guo; Bo Zhao; Haonan Guo; Yunfei Ge; Nan Sheng; Elisabetta Gariboldi; Chunyu Zhu (Chemical Engineering Journal, 2024)

Anti-epileptic and Neuroprotective Effects of Ultra-low Dose NADPH Oxidase Inhibitor Dextromethorphan on Kainic Acid-induced Chronic Temporal Lobe Epilepsy in Rats - Jing-Jing Yang; Ying-Xin Liu; Yan-Fang Wang; Bi-Ying Ge; Ying Wang; Qing-Shan Wang; Sheng Li; Jian-Jie Zhang; Ling-Ling Jin; Jau-Shyong Hong; Sheng-Ming Yin; Jie Zhao (Neuroscience Bulletin, 2024)

Semi-automatic identification of rock discontinuity orientation based on 3D point clouds and its engineering application - Jingyu Kang; Xiaodong Fu; Qian Sheng; Yunfeng Ge; Jian Chen; Haibin Wang (Bulletin of Engineering Geology and the Environment, 2024)

Inhalation exposure to polystyrene nanoplastics induces chronic obstructive pulmonary disease-like lung injury in mice through multi-dimensional assessment - Sheng Yang; Tianyi Zhang; Yiling Ge; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Pollution, 2024)

Agarose amplification based sequencing characterization cell-free RNA in preimplantation spent embryo medium - Huajuan Shi; Qinyu Ge; Min Pan; Yuqi Sheng; Ting Qi; Ying Zhou; Yuqing Sun; Yunfei Bai; Lingbo Cai (Analytica Chimica Acta, 2024)

Towards standardizing automated image analysis with artificial intelligence for biodiversity - Peng Zhou; Yu-Xin Bu; Ge-Yi Fu; Chun-Sheng Wang; Xue-Wei Xu; Xiaoyong Pan (Frontiers in Marine Science, 2024)

Ferroptosis participated in inhaled polystyrene nanoplastics-induced liver injury and fibrosis - Yiling Ge; Sheng Yang; Tianyi Zhang; Saisai Gong; Xin Wan; Yuxin Zhu; Yifei Fang; Chengyu Hu; Fei Yang; Lihong Yin; Yuepu Pu; Zaozao Chen; et al. (Science of The Total Environment, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Optically stimulated luminescence dating of Paleolithic sites reveals population shifts in North China during the last glacial period - Junyi Ge; Xiao Sun; Yan Li; Chunxue Wang; Lishuang Sheng; Ke Hu; Jiequn Hua; Xiaoling Zhang; Faxiang Huan; Shixia Yang; John W. Olsen; Xing Gao; et al. (Global and Planetary Change, 2024)

Characteristics of air pollution complex in a typical chemical industrial development zone in eastern China - Lingling Zhang; Xiaofeng Xu; Yayi Zhang; Xuyun Zhang; Jian Wu; Xia Sheng; Fei Chen; Liqin Chen; Xinlei Ge; Haisuo Wu (Atmospheric Environment, 2024)

Multiple Pathways for the Enhancement of Wheat Growth by Chlorella vulgaris - Sheng-Nan Wang; Shu-Han Ge; Lin-Lan Zhuang; Jian Zhang (Journal of Plant Growth Regulation, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

The hepatotoxicity assessment of micro/nanoplastics: A preliminary study to apply the adverse outcome pathways - Yiling Ge; Sheng Yang; Tianyi Zhang; Xin Wan; Yuxin Zhu; Fei Yang; Lihong Yin; Yuepu Pu; Geyu Liang (Science of The Total Environment, 2023)

The trait co-variation regulates the response of bryophytes to nitrogen deposition: A meta-analysis - Xu Sheng; Cai Qiying; Sun Shifeng; Liu Yizhen; Guan Bicai; Wu Lan; Ge Gang (Environmental Pollution, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Fiscal spending and green economic growth: evidence from highly polluting Asian economic - Ge Chen; Qiu Sheng Li (Environmental Science and Pollution Research, 2023)

A comparative transcriptome analysis of how shrimp endure and adapt to long-term symbiosis with Enterocytozoon hepatopenaei infection - Leiting Zhang; Sheng Zhang; Yi Qiao; Xiaowei Cao; Ge Jiang; Jie Cheng; Xihe Wan; Qingguo Meng; Hui Shen (Fish & Shellfish Immunology, 2023)

Prussian blue analogues-derived zero valent iron to efficiently activate peroxymonosulfate for phenol degradation triggered via reactive oxygen species and high-valent iron-oxo complexes - Tong Wei; Xin-Sheng Zhu; Qi-Xue Wang; Ke-Ke Xu; Fu-Kai Tang; Ming-Zhu Zhang; Shi-Wen Lv; Feng Ge (Environmental Research, 2023)

Sentinel supervised lung-on-a-chip: A new environmental toxicology platform for nanoplastic-induced lung injury - Sheng Yang; Tianyi Zhang; Yiling Ge; Yanping Cheng; Lihong Yin; Yuepu Pu; Zaozao Chen; Geyu Liang (Journal of Hazardous Materials, 2023)

In-situ pyrolysis kinetic analysis and fixed-bed pyrolysis behavior of ex-service wind turbine blades - Yuqing Wu; Zefeng Ge; Chen Huang; Zhenting Zha; Mingxun Zeng; Yuna Ma; Lijuan Sun; Zenghui Hou; Sheng Chu; Huiyan Zhang (Waste Management, 2023)

Inoculation with thermophiles enhanced the food waste bio-drying and complicated interdomain ecological networks between bacterial and fungal communities - Fucheng Teng; Ge Tan; Tianbo Liu; Teng Zhang; Yongjun Liu; Sheng Li; Can Lei; Xing Peng; Huaqun Yin; Delong Meng (Environmental Research, 2023)

Distribution pattern of planktonic and benthic foraminifera in surface sediments near the equatorial western Indian Ocean and its indications of paleo-environment and productivity - Wei Shen; Shuqing Qiao; Rongtao Sun; Zhoutian He; Bin Wu; Lina Jin; Liang Chen; Zhengxin Yin; Chendong Ge; Xuefa Shi; Jie Sheng (Journal of Asian Earth Sciences, 2023)

Catalytic oxidation of toluene over V, Ce and Mo doped Cu/γ-Al2O3 in SO2-containing flue gas: Study of metal doping effect and reaction pathway - Yue Lyu; Jingying Xu; Qingquan Cao; Sheng Chen; Shuai Ge (Fuel, 2023)

Phosphorus amendment alters soil arbuscular mycorrhizal fungal functional guild compositions in a subtropical forest - Quan-Cheng Wang; Sheng-Sheng Jin; Shanshan Liu; Ge Song; Chunjian Duan; Peng-Peng Lü; Pulak Maitra; Lin Xie; Yongxin Lin; Hang-Wei Hu; Ji-Zheng He; Yong Zheng (Journal of Soils and Sediments, 2023)

Urban vitality assessment at the neighborhood scale with geo-data: A review toward implementation - Sheng Liu; Jian Ge; Xinyue Ye; Chao Wu; Ming Bai (Journal of Geographical Sciences, 2023)

Engineered urinary-derived extracellular vesicles loaded nanoenzymes as Trojan horses to regulate the inflammatory microenvironment for treatment of Alzheimer's disease - Zetai Bai; Kezhen Ge; Jingjing Fu; Dehong Yu; Zhiyuan Hua; Senlin Xue; Zheng Li; Weiwei Sheng; Xiunan Wu; Fenfang Gao; Deqin Geng; Fenglei Gao (Chemical Engineering Journal, 2023)

Association Between IL10 Polymorphisms and the Susceptibility to Sepsis: A Meta-Analysis - Ning Zhang; Siting Wang; Yipan Fan; Changding Sheng; Weixing Ge (Biochemical Genetics, 2023)

Causes of the discordance in the south-north distribution of the 2017 Jiuzhaigou earthquake sequences - Zhi-Tong Jin; Jia-Lu Liu; Yong-Ge Wan; Shu-Zhong Sheng; Fu-Chang Wang; Xiao-Tao Zhang; Gan Feng (Applied Geophysics, 2023)

Metal-immobilizing Pseudomonas taiwanensis WRS8 reduces heavy metal accumulation in Coriandrum sativum by changing the metal immobilization–related bacterial population abundances - Yanyan Ge; Zhenyu Wen; Linyan He; Xiafang Sheng (Environmental Science and Pollution Research, 2023)

Understanding the shortboard of regional sustainable development: fairness and efficiency of rural public resource allocation in China - Sheng Zhang; Ge Li; Ran Yu; Yuanhua Chang; Yifu Yang; Qihao Zhang; Weining Liu; Jiming Hao (Environment, Development and Sustainability, 2023)

Experimental investigation of the seismic performance of precast post-tensioned segmental bridge piers with stainless energy-dissipating bars - Jian-Yu Fu; Xiao Ge; Jian-Tao Li; Zhi-Guo Sun; Hui Qian; Dong-Sheng Wang (Engineering Structures, 2023)

Capped L21-norm-based common spatial patterns for EEG signals classification applicable to BCI systems - Jingyu Gu; Jiuchuan Jiang; Sheng Ge; Haixian Wang (Medical & Biological Engineering & Computing, 2023)

EchoAI: A deep-learning based model for classification of echinoderms in global oceans - Zhinuo Zhou; Ge-Yi Fu; Yi Fang; Ye Yuan; Hong-Bin Shen; Chun-Sheng Wang; Xue-Wei Xu; Peng Zhou; Xiaoyong Pan (Frontiers in Marine Science, 2023)
Introduction In response to the need for automated classification in global marine biological studies, deep learning is applied to image-based classification of marine echinoderms. Methods Images of marine echinoderms are collected and classified according to their systematic taxonomy. The images belong to 5 classes, 38 orders, 145 families, 459 genera, and 1021 species, respectively. The deep learning model, EfficientNetV2, outperforms the competing model and is chosen for developing the automated classification tool, EchoAI. Then, the EfficientNetV2-based tool, EchoAI is applied to each taxonomic level. Results The accuracy for the test dataset was 0.980 (class), 0.876 (order), 0.738 (family), 0.612 (genus), and 0.469 (species), respectively. Online prediction service is provided. Discussion The EchoAI model and results are facilitated for investigating the diversity, abundance and distribution of species at the global scale, and the methodological strategy can also be applied to image classification of other categories of marine organisms, which is of great significance for global marine studies. EchoAI is freely available at http://www.csbio.sjtu.edu.cn/bioinf/EchoAI/ for academic use.

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

Covalent organic framework membranes for acid recovery: The effect of charges - Fangmeng Sheng; Yuan Xia; Zhang Zhao; Tingting Xu; Liang Ge; Xingya Li; Tongwen Xu (Chemical Engineering Journal, 2023)

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Transforming municipal cotton waste into a multilayer fibre biocomposite with high strength - Yang Shi; Jinxuan Jiang; Haoran Ye; Yequan Sheng; Yihui Zhou; Shin Ying Foong; Christian Sonne; William Woei Fong Chong; Su Shiung Lam; Yanfei Xie; Jianzhang Li; Shengbo Ge (Environmental Research, 2023)

Genome‐scale signatures of adaptive gene expression changes in an invasive seaweed Gracilaria vermiculophylla - Jin‐Xi Xiang; Mahasweta Saha; Kai‐Le Zhong; Quan‐Sheng Zhang; Di Zhang; Alexander Jueterbock; Stacy A. Krueger‐Hadfield; Gao‐Ge Wang; Florian Weinberger; Zi‐Min Hu (Molecular Ecology, 2023)
Invasive species can successfully and rapidly colonize new niches and expand ranges via founder effects and enhanced tolerance towards environmental stresses. However, the underpinning molecular mechanisms (i.e., gene expression changes) facilitating rapid adaptation to harsh environments are still poorly understood. The red seaweed Gracilaria vermiculophylla , which is native to the northwest Pacific but invaded North American and European coastal habitats over the last 100 years, provides an excellent model to examine whether enhanced tolerance at the level of gene expression contributed to its invasion success. We collected G. vermiculophylla from its native range in Japan and from two non‐native regions along the Delmarva Peninsula (Eastern United States) and in Germany. Thalli were reared in a common garden for 4 months at which time we performed comparative transcriptome (mRNA) and microRNA (miRNA) sequencing. MRNA‐expression profiling identified 59 genes that were differently expressed between native and non‐native thalli. Of these genes, most were involved in metabolic pathways, including photosynthesis, abiotic stress, and biosynthesis of products and hormones in all four non‐native sites. MiRNA‐based target‐gene correlation analysis in native/non‐native pairs revealed that some target genes are positively or negatively regulated via epigenetic mechanisms. Importantly, these genes are mostly associated with metabolism and defence capability (e.g., metal transporter Nramp5, senescence‐associated protein, cell wall‐associated hydrolase, ycf68 protein and cytochrome P450‐like TBP). Thus, our gene expression results indicate that resource reallocation to metabolic processes is most likely a predominant mechanism contributing to the range‐wide persistence and adaptation of G. vermiculophylla in the invaded range. This study, therefore, provides molecular insight into the speed and nature of invasion‐mediated rapid adaption.

Comprehensive profiles of per- and polyfluoroalkyl substances in Chinese and African municipal wastewater treatment plants: New implications for removal efficiency - Lulin Jiang; Jingzhi Yao; Ge Ren; Nan Sheng; Yong Guo; Jiayin Dai; Yitao Pan (Science of The Total Environment, 2023)

Amphiphilic ligand in situ assembly of uranyl active sites and selective interactions of molybdenum disulfide - Yuhui Liu; Yaning Lu; Shuang Zhang; Xiaoyan Li; Zhibin Zhang; Liya Ge; MengYu Chang; Yunhai Liu; Grzegorz Lisak; Sheng Deng (Journal of Hazardous Materials, 2023)

Association of soft drink and 100% fruit juice consumption with all-cause mortality, cardiovascular diseases mortality, and cancer mortality: A systematic review and dose-response meta-analysis of prospective cohort studies - Bei Pan; Long Ge; Honghao Lai; Qi Wang; Qi Wang; Qian Zhang; Min Yin; Sheng Li; Jinhui Tian; Kehu Yang; Jiancheng Wang (Critical Reviews in Food Science and Nutrition, 2022)

Soil microbe inoculation alters the bacterial communities and promotes root growth of Atractylodes lancea under heat stress - Hongyang Wang; Yuefeng Wang; Daiquan Jiang; Zengxu Xiang; Sheng Wang; Chuanzhi Kang; Wenjin Zhang; Yang Ge; Tielin Wang; Luqi Huang; Dahui Liu; Lanping Guo (Plant and Soil, 2022)

RETRACTED: Amplitude and Phase Computable Ocean Wave Real-Time Modeling with GPU Acceleration - Guigui Wang; Shihan Tan; Ge Song; Sheng Wang (Journal of Marine Science and Engineering, 2022)
The CBATS (carrier-based aircraft take-off and landing training system) is an important application of virtual reality technology in the simulation field. Large-scale, real-time ocean simulations are the biggest challenge to the authenticity of the visual system of CBATS and are also currently the main research hotspot in the field of computer graphics. In this paper, a hybrid Ocean Modeling Method based on wavelet transform is presented. This method introduces an accurate phase calculation and a wind-field model solution to compensate for the randomness of wave generation and the lack of physical mechanism in spectral methods. The computational cost is greatly reduced by using a rough spatial grid to calculate the amplitude and phase values at any point in space, which effectively avoids Nyquist–Shannon Theorem limitations caused by the numerical solutions of PDEs (partial differential equations), and a high-fidelity simulation of high frequency, detailed sea surface and coherent phase-dependent wave effects is achieved. Practical verification shows that the method can fully meet the real-time simulation training requirements of CBATS with a strong real-time performance and good stability. Thus, it could play a significant role in improving the performance of the visual system.

Research Progress on Volatile Organic Compounds Emissions from Coal-fired Power Plants - Jingxin Xu; Fahua Zhu; Xinlei Ge; Haiwei Li; Xiuyong Zhao; Wenxin Tian; Xi Zhang; Yuan Bai; Fengxia An; Sheng Wang (Current Pollution Reports, 2022)

Exploration of walnut components and their association with health effects - Zhi-Jing Ni; Yi-Ge Zhang; Sheng-Xiong Chen; Kiran Thakur; Shaoyun Wang; Jian-Guo Zhang; Ya-Fang Shang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2022)

Scholte wave dispersion and particle motion mode in ocean and ocean crust - Xu Xin; Wan Yong-Ge; Li Zhen-Yue; Sheng Shu-Zhong (Applied Geophysics, 2022)

Atmospheric Disturbance Characteristics in the Lower-middle Stratosphere Inferred from Observations by the Round-Trip Intelligent Sounding System (RTISS) in China - Yang He; Xiaoqian Zhu; Zheng Sheng; Wei Ge; Xiaoran Zhao; Mingyuan He (Advances in Atmospheric Sciences, 2022)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Study on the crustal stress field of the Tengchong volcanic area using composite focal mechanism method - Shu-zhong Sheng; Yong-ge Wan; Chang-sheng Jiang; Xiao-shan Wang; Shan-shan Liang; Gen-ru Xiao; Xiao-hui Hu (Applied Geophysics, 2021)

Slope structures and formation of rock-soil aggregate landslides in deeply incised valleys - Yong-jian Bai; Yun-sheng Wang; Hua Ge; Yong-bo Tie (Journal of Mountain Science, 2020)

Study on the Clinical Features and Prognosis of Penicilliosis marneffei Without Human Immunodeficiency Virus Infection - Ying-ge Wang; Jin-mei Cheng; Hai-bo Ding; Xi Lin; Guo-hao Chen; Mei Zhou; Sheng-nan Ye (Mycopathologia, 2018)

Livelihood differentiation between two villages in Yesanpo Tourism District in China - Tai Huang; Jian-chao Xi; Quan-sheng Ge (Journal of Mountain Science, 2017)

Acoustic Emission Characteristics of Sedimentary Rocks Under High-Velocity Waterjet Impingement - Shouceng Tian; Mao Sheng; Zhaokun Li; Hongkui Ge; Gensheng Li (Rock Mechanics and Rock Engineering, 2017)

Production of β-carotene by expressing a heterologous multifunctional carotene synthase in Yarrowia lipolytica - Shuliang Gao; Yangyang Tong; Li Zhu; Mei Ge; Yu Jiang; Daijie Chen; Sheng Yang (Biotechnology Letters, 2017)

Microbial profiles of a drinking water resource based on different 16S rRNA V regions during a heavy cyanobacterial bloom in Lake Taihu, China - Junyi Zhang; Congming Zhu; Rui Guan; Zhipeng Xiong; Wen Zhang; Junzhe Shi; Yi Sheng; Bingchuan Zhu; Jing Tu; Qinyu Ge; Ting Chen; Zuhong Lu (Environmental Science and Pollution Research, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Three new sulphur glycosides from the seeds of Descurainia sophia - Wei-sheng Feng; Chun-Ge Li; Xiao-Ke Zheng; Ling-Ling Li; Wen-Jing Chen; Yan-Li Zhang; Yan-Gang Cao; Jian-Hong Gong; Hai-Xue Kuang (Natural Product Research, 2016)

Development polymorphic microsatellite primers for the giant panda’s staple food bamboo Bashania fargesii and B. aristata (Poaceae: Bambusoideae) - Ge Yu; Jian-Jun Liu; Qing-Qing Ma; Yi-Sheng Ma (Conservation Genetics Resources, 2015)

Village network centrality in rural tourism destination: A case from Yesanpo tourism area, China - Rui-ying Zhang; Jian-chao Xi; Shou-kun Wang; Xin-ge Wang; Quan-sheng Ge (Journal of Mountain Science, 2015)

One-step integration of multiple genes into the oleaginous yeast Yarrowia lipolytica - Shuliang Gao; Linna Han; Li Zhu; Mei Ge; Sheng Yang; Yu Jiang; Daijie Chen (Biotechnology Letters, 2014)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

C-type natriuretic peptide inhibiting vascular calcification might involve decreasing bone morphogenic protein 2 and osteopontin levels - Jing-Jing Chen; Jing Zhang; Yan Cai; Ye-Bo Zhou; Ge-Bo Wen; Chao-Shu Tang; Yong-Fen Qi; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2014)

A new antibacterial lipopeptide found by UPLC-MS from an actinomycete Streptomyces sp. HCCB10043 - Min Rao; Wei Wei; Mei Ge; Daijie Chen; Xiafang Sheng (Natural Product Research, 2013)

Acrylamide biodegradation ability and plant growth-promoting properties of Variovorax boronicumulans CGMCC 4969 - Zhong-Hua Liu; Yu-Min Cao; Qian-Wen Zhou; Kun Guo; Feng Ge; Jun-Yi Hou; Si-Yi Hu; Sheng Yuan; Yi-Jun Dai (Biodegradation, 2013)

Molecular basis for insecticide‐enhanced thermotolerance in the brown planthopper N ilaparvata lugens S tål ( H emiptera: D elphacidae) - Lin‐Quan Ge; Liu‐Juan Huang; Guo‐Qin Yang; Qi‐Sheng Song; David Stanley; G. M. Gurr; Jin‐Cai Wu (Molecular Ecology, 2013)
Climate change is likely to have marked ecological effects on terrestrial ecosystems, including the activities of insect pests. Most attention has focused on the increasing geographical ranges of pests; however, if extrinsic factors enhance their thermotolerance, populations may express increased voltinism and longer daily and annual activity periods. These changes in pest populations have the potential for severe consequences, including increased crop losses and decreased food security at the global level. The brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) is a serious pest of rice crops in temperate and tropical regions of Asia. It is often present in rice microclimates at temperatures close to its maximum thermotolerance. Recent BPH outbreaks in tropical Asia are considered to be associated with excess use of pesticides and increasing temperature. This study tested whether exposure to sublethal concentrations of triazophos (tzp), an insecticide widely used in Asian rice production, enhances thermotolerance of BPH . Tzp exposure (40 ppm at 40 °C) significantly decreased mortality (from 94% in controls to 50% at 48 h post‐treatment) and increased lethal mean time ( LT 50 ) of adults by 17.2 h. To investigate the underlying molecular mechanism of this tzp‐enhanced thermotolerance, we selected Hsp70 and Arginine kinase (Argk) for detailed study. Transcripts encoding both proteins in third‐instar nymphs and brachypterous adult females were up‐regulated, compared with controls, after exposure to tzp. RNA i silencing of both genes demonstrated that Hsp70 and Argk are essential for survival and tzp‐increased thermotolerance. We propose that tzp induces thermotolerance in BPH s by increasing the expression of genes that act in cell protection mechanisms. The significance of our proposal relates to the importance of understanding the influence of sublethal concentrations of insecticides on pest biology. In addition to its influence on thermotolerance, tzp also enhances BPH reproduction. We infer that exposure to a pesticide stressor can produce cross‐tolerance, that is, increased tolerance to one stressor also increases tolerance to other stressors, including temperature. Aside from needing a better understanding of these effects in nature and in other pest/cropping systems, we suggest that pest management programmes can be improved with better understanding of the influences of stressors, including increased environmental temperatures and sublethal concentrations of insecticides, on pest biology.

Precipitation variations in Beijing during 1860–1897 AD revealed by daily weather records from the Weng Tong‐He Diary - Xue‐Zhen Zhang; Quan‐Sheng Ge; Xiu‐Qi Fang; Jing‐Yun Zheng; Jie Fei (International Journal of Climatology, 2013)
Daily weather records from a historical private diary provide important data for studying historical climate change. We compiled daily weather records from the Weng Tong‐He Diary and counted the number of monthly precipitation days during 1860‐1897 AD for Beijing; then, using the number of monthly precipitation days, we reconstructed the seasonal precipitation using regression models relating the precipitation and precipitation days. The findings show that the monthly mean number of precipitation days for 1860‐1897 was greater than that for 1951‐2009 by about 1 d month −1 and that the summer (June to August, JJA) precipitation for 1860‐1897 was 471.8 mm greater than that for 1951‐2009 by about 15.5%. The JJA precipitation of 1860‐1897 had not only inter‐annual variations but also inter‐decadal variations that were characterized by less precipitation before 1886 (about 421.9 mm) and more precipitation thereafter (about 550.7 mm). As a consequence, the JJA precipitation of 1860‐1897 showed an evident positive trend with a rate of about 57.9 mm per decade. These precipitation variations were confirmed by other datasets. However, it is worth noting that our reconstruction underestimates the historical precipitation values (by about 22.5%) because of rainfall/snowfall events missed in Weng's diary and the poor ability of the regression models to capture extreme years. In the future, new methods of reconstructing precipitation with the consideration of missed rainfall/snowfall events are needed. Copyright © 2012 Royal Meteorological Society

Molecular epidemiology of hepatitis C virus among different groups of people in the province of Fujian, China - Ying Ye; Yan-sheng Yan; Ge Chen; Ping-ping Yan; Wu-xiong Zheng; Yan-qin Deng; Xiu-hui Yang; Shou-li Wu; Zhi-shan Zhang (Archives of Virology, 2013)

Seasonal migration by a large forest ungulate: a study on takin (Budorcas taxicolor) in Sichuan Province, China - Tian-Pei Guan; Bao-Ming Ge; William J. McShea; Sheng Li; Yan-Ling Song; Chad M. Stewart (European Journal of Wildlife Research, 2013)

MTHFR C677T polymorphism contributes to colorectal cancer susceptibility: evidence from 61 case–control studies - Xuewen Sheng; Yanxi Zhang; Erjiang Zhao; Su Lu; Xiaoli Zheng; Hong Ge; Weiquan Lu (Molecular Biology Reports, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

PDGF-AA Mediates B104CM-Induced Oligodendrocyte Precursor Cell Differentiation of Embryonic Neural Stem Cells Through Erk, PI3K, and p38 Signaling - Jian-Guo Hu; Yan-Xia Wang; Hong-Ju Wang; Ming-Sheng Bao; Zhen-Huan Wang; Xin Ge; Feng-Chao Wang; Jian-Sheng Zhou; He-Zuo Lü (Journal of Molecular Neuroscience, 2012)

Rapid and Sensitive Detection of Listeria monocytogenes by Loop-Mediated Isothermal Amplification - Meng-Jun Tang; Sheng Zhou; Xiao-Yan Zhang; Jun-Hua Pu; Qing-Lian Ge; Xiu-Jun Tang; Yu-Shi Gao (Current Microbiology, 2011)

Antiviral activity and possible mechanisms of action of pentagalloylglucose (PGG) against influenza A virus - Ge Liu; Sheng Xiong; Yang-Fei Xiang; Chao-Wan Guo; Feng Ge; Chong-Ren Yang; Ying-Jun Zhang; Yi-Fei Wang; Kaio Kitazato (Archives of Virology, 2011)

A 35-GHz polarimetrie Doppler radar and its application for observing clouds associated with Typhoon Nuri - Lingzhi Zhong; Lipingt Liu; Sheng Feng; Runsheng Ge; Zhe Zhang (Advances in Atmospheric Sciences, 2011)

Weight-reducing effect of Acer truncatum Bunge may be related to the inhibition of fatty acid synthase - Wen-Hua Zhao; Li-Fang Gao; Wen Gao; Yong-Sheng Yuan; Chun-Chun Gao; Li-Ge Cao; Zi-Zheng Hu; Jian-Qiang Guo; Ying-Xia Zhang (Natural Product Research, 2011)

Phenylpropanoid and flavonoids from osteoprotective fraction of Drynaria fortunei - Xin-Luan Wang; Nai-Li Wang; Hao Gao; Ge Zhang; Ling Qin; Man-Sau Wong; Xin-Sheng Yao (Natural Product Research, 2010)

Nine novel microsatellite markers for the hog deer (Axis porcinus) - Hong Lian; Jian-Qiu Yu; Yun-Fa Ge; Sheng-Guo Fang (Conservation Genetics, 2009)

Eight polymorphic microsatellite loci for the Chinese medicinal plant Artemisia annua L. (Asteraceae) - Hui-Run Huang; Guang Zhou; Xue-Jun Ge; Xiao Wei; Yun-Sheng Jiang; Hui Tang (Conservation Genetics, 2009)

Autophagy is activated and might protect neurons from degeneration after traumatic brain injury - Yan-Bo Zhang; Sheng-Xing Li; Xi-Ping Chen; Li Yang; Yun-Ge Zhang; Ran Liu; Lu-Yang Tao (Neuroscience Bulletin, 2008)

Eight novel microsatellite markers from the Père David’s deer (Elaphurus davidianus) - Yang Jiao; Yun-Fa Ge; Sheng-Guo Fang (Conservation Genetics, 2008)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Isolation and characterization of a novel cDNA encoding ERF/AP2-type transcription factor OsAP25 from Oryza Sativa L. - Xiao-Yan Fu; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jin-Ge Liu; Li-Juan Wu; Feng Gao; Hong Zhu; Zhao-Kui Guo; Quan-Hong Yao (Biotechnology Letters, 2007)

Isolated and characterization of a cDNA encoding ethylene-responsive element binding protein (EREBP)/AP2-type protein, RCBF2, in Oryza sativa L. - Jin-Ge Liu; Zhen Zhang; Qiu-Lin Qin; Ri-He Peng; Ai-Sheng Xiong; Jian-Min Chen; Fang Xu; Hong Zhu; Quan-Hong Yao (Biotechnology Letters, 2006)

Reliable genetic analyses based on formalin-fixed materials: a new noninvasive sampling perspective for the giant panda - Qiu-Hong Wan; Jian-Qiu Yu; Yan-Ge Yong; Sheng-Guo Fang (Conservation Genetics, 2006)

Signal role for activation of caspase-3-like protease and burst of superoxide anions during Ce4+-induced apoptosis of cultured Taxus cuspidata cells - Zhi-Qiang Ge; Song Yang; Jing-Sheng Cheng; Ying-Jin Yuan (BioMetals, 2005)

Effects of organic solvents on membrane ofTaxus cuspidata cells in - Qiu-man Xu; Jing-sheng Cheng; Zhi-qiang Ge; Ying-jin Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Analysis of driving forces on the change of historical farmland use in Shandong province during the Qing Dynasty (1644–1911) - Xue-qin Zhang; Quan-sheng Ge; Jing-yun Zheng (Chinese Geographical Science, 2003)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)